APPLICATION OF INTERACTIVE TEACHING METHOD IN PROGRAMMING ENGINEERING COURSE FOR STUDENTS OF THE FACULTY OF INFORMATION TECHNOLOGY, UNIVERSITY OF INFORMATION AND COMMUNICATION TECHNOLOGY, THAI NGUYEN UNIVERSITY - Duong Thi Quy, Tran Duy Minh (Tạp chí Khoa học, 2024)
Interactive teaching methods have been receiving attention in application to innovate teaching methods in education and training, especially in training human resources in technical fields. With the participation of computers and supporting software, along with other means, the interaction process between teacher - learner - environment increasingly plays an important role in forming knowledge and skills for learners. For the University of Information and Communication Technology, Thai Nguyen University, Thai Nguyen University, interactive teaching methods are applied in training Information Technology students flexibly in each subject to improve education quality. Through survey methods and other research methods, the article analyses the actual conditions for applying interactive teaching methods in Programming Engineering course for students of the Faculty of Information Technology, University of Information and Communication Technology, Thai Nguyen University, from which the limitations will be evaluated. On that basis, the article offers some measures to improve the effectiveness of applying interactive teaching methods in Programming Engineering for students.